SEJARAH HUKUM PERBANKAN SYARIAH DI INDONESIA - Iman Nur Hidayat; Nurizal Ismail; Alifia Annisaa (Universitas Darussalam Gontor, 2019)
Since 1934, the idea to establish an Islamic bank hasarisen. It began with the concept that the banks’ interest isharam. Then the establishment of Bank Perkreditan Rakyat(BPR) which used zero interest in its operational system. MUIbanking team was established in 1992, after Lokakarya BungaBank MUI, to manage the establishment of first Islamic bank,namely Bank Muamalat Indonesia on 1 November 1991.In era law no. 10 of 1998, dual banking system appeared,and the acknowledgement of three banking types existencebegan in law 21 of 2008 because those were mentioned inlaw no. 21 of 2008. The method used in this research is ahistorical method, in which search for data and facts frompast that has correlations with the implementation of Islamicbanking from the first establishment until 2014 (1992-2014)then recite it in this research. The finding revealed that theexistence of legal act (Law No. 21 of 2008) have been giving anincrease in the number of Sharia Commercial Banks whichwere originally only three Islamic Commercial Banks (BUS)up to 14. This can be an input for the government that forall sharia-compliant matters such as sharia insurance, shariamutual funds, Islamic capital markets, and others, it requireslegal aspects from the government that regulate it so that thedevelopment of Sharia economy in Indonesia will accelerate.